Pendidikan Kesehatan tentang Sosialisasi Kesehatan Remaja tentang Gizi dan Seksual di MTS Yapensa Jenggot Kota Pekalongan - Ida Baroroh; Hilda Prajayanti (LPPM Akbid Harapan Ibu Pekalongan, 2020)
Teenagers Are Residents In The Age Range Of 10-19 Years. The Age Range Of Adolescents Is 10-24 Years And Not Married (Who, 2014). Adolescence Is A Period Of Rapid Growth And Development Either Physically, Psychologically And Intellectually. The Special Nature Of Adolescents Are Has A Great Sense Of Curiosity, Likes Adventure And Challenges And Tends To Dare To Bear The Risk Of His Actions Without Being Preceded By Careful Consideration. If Decisions Taken In The Face Of Conflict Are Inappropriate, They Will Fall Into Risky Behavior And May Suffer Short-Term And Long-Term Consequences In A Variety Of Physical And Psychosocial Health Problems (Ministry Of Health, 2014). The Aim Of Community Service Is To Provide Adolescent Health Education About Nutrition And Sexual. Health Education Methods Carried Out Are (1) Socialization And Licensing, (2) Conducting Adolescent Health Education About Nutrition And Sexual. (3) Evaluation Of The Results Of Health Education Activities. The Results Of The Health Education Activity Showed High Enthusiasm Shown By The Participants' Very Good Response In Receiving Material About Adolescent Health Education On Nutrition And Sexual As Well As The Willingness Of Participants To Ask Questions. The Enthusiasm Of The Participants Is Expected To Increase Students' Understanding Of The Importance Of Balanced Nutrition And Sexual Health.